Sant Serni davant el capitoli de Tolosa de Llenguadoc beneint el brau, objecte del seu martiri. Nou mural romànic a Sorpe - Pagès i Paretas, Montserrat (Miscel·lània litúrgica catalana, 2016)
The author studies a new Romanesque mural, just discovered, whose subject is that of the title of this paper. This constitutes a new image in the catalogue of Romanesque iconography of the martyr of Toulouse and apostle to the Gauls. The author identifies the subject and explores the implications of the find: what this scene means in that place and what can be deduced from it: in the now-destroyed apse there may have been depicted the martyrdom of Saturninus with his legs bound to the bull and the beast dragging the saint down the steps of the Toulouse Capitole. The article attempts to make a stylistic ascription of the mural to one of the painters who worked on the churchs decoration.